Effect of impeller type on cellular morphology and production of clavulanic acid by Streptomyces clavuligerus - Bustamante, M. C.C.; Costa, C. L.L.; Esperança, M. N.; Mazziero, V. T. [UNESP]; Cerri, M. O. [UNESP]; Badino, Alberto C. (Springer Nature, 2024)
It is essential to evaluate the effects of operating conditions in submerged cultures of filamentous microorganisms. In particular, the impeller type influences the flow pattern, power consumption, and energy dissipation, leading to differences in the hydrodynamic environment that affect the morphology of the microorganism. This work investigated the effect of different impeller types, namely the Rushton turbine (RT-RT) and Elephant Ear impellers in up-pumping (EEUP) and down-pumping (EEDP) modes, on cellular morphology and clavulanic acid (CA) production by Streptomyces clavuligerus in a stirred-tank bioreactor. At 800 rpm and 0.5 vvm, the cultivations performed using RT-RT and EEUP impellers provided higher shear conditions and oxygen transfer rates than those observed with EEDP. These conditions resulted in higher clavulanic acid production using RT-RT (380.7 mg/L) and EEUP (453.3 mg/L) impellers, compared to EEDP (196.6 mg/L). Although the maximum CA concentration exhibited the same order of magnitude for RT-RT and EEUP impellers, the latter presented 40% of the specific power consumption (4.9 kW/m3) compared to the classical RT-RT (12.0 kW/m3). The specific energy for CA production (ECA), defined as the energy cost to produce 1 mg of CA, was 3.5 times lower using the EEUP impeller (1.91 kJ/mgCA) when compared to RT-RT (5.91 kJ/mgCA). Besides, the specific energy for O2 transfer (EO2), the energy required to transfer 1 mmol of O2, was 2.3 times lower comparing the EEUP impeller (3.28 kJ/mmolO2) to RT-RT (7.65 kJ/mmolO2). The results demonstrated the importance of choosing the most suitable impeller configuration in conventional bioreactors to manufacture bioproducts. Graphical abstract: (Figure presented.)
Keywords: Clavulanic acid; Elephant ear impeller; Rushton turbine; Shear rate; Stirred-tank bioreactor; Streptomyces clavuligerus